2017
DOI: 10.1016/j.tcr.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Double-plate fixation in double clavicle fractures: A case report

Abstract: Bilateral clavicle fractures are rare; Double clavicle fractures are particularly rare. We report a case of a 23-year-old woman presenting with double fractures (middle and distal end) of the right clavicle and single fracture of the left clavicle after she suffered a road traffic accident. Four days after the injury, the right clavicle was fixed with a reconstruction locking plate and a hook plate, the left clavicle was fixed by a S-shaped locking plate. Bone union was achieved 3 months after surgery. The pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Qi, et al study demonstrated how the right clavicle fixation was done with a reconstruction locking plate and a hook plate, and the left clavicle was fixed with an S-shaped locking plate. They achieved bone union at three months following surgery and concluded that double-plate fixation successfully achieved excellent long-term outcomes [ 6 ]. According to various authors, surgical choice differs; in our study, we emphasize considering patient factors before employing surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Qi, et al study demonstrated how the right clavicle fixation was done with a reconstruction locking plate and a hook plate, and the left clavicle was fixed with an S-shaped locking plate. They achieved bone union at three months following surgery and concluded that double-plate fixation successfully achieved excellent long-term outcomes [ 6 ]. According to various authors, surgical choice differs; in our study, we emphasize considering patient factors before employing surgical management.…”
Section: Discussionmentioning
confidence: 99%
“…Although fractures of the clavicle are among the most frequent fractures in adults, simultaneous traumatic bilateral clavicle fractures in adults are reported more rarely [5][6][7][8]. Based on the few published reports, bilateral clavicle fractures represent less than 0.5% of all clavicle fractures [6,9].…”
Section: Introductionmentioning
confidence: 99%